Chemical characterisation of printed circuit board wastewater. - Sobri, Shafreeza; Ali, A. H. M. (2011)
Manufacturing of PCBs is highly complicated and involves many processes. Recycling of PCB wastewater receives wide concerns as the recent international growth in the electronics industry has generated a drastic increase in the amount of waste PCBs with profound environmental impacts such as soil and groundwater contamination. This paper reports on the chemical characterization of PCB wastewater as the initial investigation for selective metal recovery.